Produção de enterocina em soro de leite parcialmente desmineralizado e água de maceração de milho - Schueler, Janaina (2018)
The production of bacteriocin by Lactic Acid Bacteria has attracted great attention because of its GRAS (Generally Recognized as Safe) status, and its potential use as a safe additive for food preservation. Due to their antimicrobial characteristics, bacteriocins have been tested as bioconservatives in several products, showing activity against pathogenic microorganisms. However, the high cost of production has still been a relevant factor for the wide use of this type of preservative. Therefore, the objective of this work was to evaluate the viability of enterocin production using partially demineralized whey and corn steep liquor as substrate. Five Enterococcus isolates (Efm20, Efm22, Efm24, Efm25 and Efs27) were tested on MRS medium against Listeria innocua CLIP 12612 bacterium and Listeria monocytogenes 2032. The MRS culture medium was replaced at 25% concentration by whey or corn steep liquor.The assay of the action of enterocin was performed by the well diffusion method. The proteinic character of bacteriocina was confirmed after incubation with proteolytic enzymes α-chymotrypsin, protease and proteinase-K. The production of hydrogen peroxide and lactic acid were discarded by the use of catalase and neutralization with NaOH. The cell free supernatant (CFS) obtained on both substrates were treated at 80 ° C and 100 ° C, exhibiting thermostability. The CFS obtained in MRS with corn steep liquor by the Efm22 isolate (24 hours) reached 6400 AU / mL against the two indicator bacteria. On the other hand, the isolates Efm24 (24 hours) and Efm20 (18 hours) reached 6400 AU / mL compared to Listeria innocua CLIP 12612. In whey, the highest values of UA / mL occurred with the isolates Efm20, Efm25 and Efs27 (24 hours). In conclusion, it was verified that the substrates tested have potential to be applied in the manufacture of food product bioconservants.